Coding and decoding libraries of sequence-defined functional copolymers synthesized via photoligation - Zydziak, Nicolas; Konrad, Waldemar; Feist, Florian; Afonin, Sergii; Weidner, Steffen; Barner-Kowollik, Christopher (Nature communications, 2016)
Designing artificial macromolecules with absolute sequence order represents a considerable challenge. Here we report an advanced light-induced avenue to monodisperse sequence-defined functional linear macromolecules up to decamers via a unique photochemical approach. The versatility of the synthetic strategy—combining sequential and modular concepts—enables the synthesis of perfect macromolecules varying in chemical constitution and topology. Specific functions are placed at arbitrary positions along the chain via the successive addition of monomer units and blocks, leading to a library of functional homopolymers, alternating copolymers and block copolymers. The in-depth characterization of each sequence-defined chain confirms the precision nature of the macromolecules. Decoding of the functional information contained in the molecular structure is achieved via tandem mass spectrometry without recourse to their synthetic history, showing that the sequence information can be read. We submit that the presented photochemical strategy is a viable and advanced concept for coding individual monomer units along a macromolecular chain. Controlling the molecular sequence of polymers and oligomers is a challenging task. Here the authors use a photoligation approach to synthesise macromolecules with functionality at defined positions throughout the chain, and additionally decode the sequence information via tandem mass spectrometry.